2019
DOI: 10.1111/ijd.14452
|View full text |Cite
|
Sign up to set email alerts
|

A Tunisian family with a novel mutation in the gene CYP4F22 for lamellar ichthyosis and co‐occurrence of hearing loss in a child due to mutation in the SLC26A4 gene

Abstract: Background Co‐occurrence of two genetic diseases is challenging for accurate diagnosis and genetic counseling. The recent availability of whole exome sequencing (WES) has dramatically improved the molecular diagnosis of rare genetic diseases in particular in consanguineous populations. Methods We report here on a consanguineous family from Southern Tunisia including three members affected with congenital ichthyosis. The index case had a hearing loss (HL) and ichthyosis and was primarily suspected as suffering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another impact of the elevated rate of consanguinity and inbreeding is the cooccurrence of two or more phenotypes within the same family [42]. Comorbidity, described particularly in inbred populations, makes genetic counseling and prenatal diagnosis challenging [42,44]. The study of Romdhane and her colleagues revealed 75 genetic disease co-occurrences identified in Tunisian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another impact of the elevated rate of consanguinity and inbreeding is the cooccurrence of two or more phenotypes within the same family [42]. Comorbidity, described particularly in inbred populations, makes genetic counseling and prenatal diagnosis challenging [42,44]. The study of Romdhane and her colleagues revealed 75 genetic disease co-occurrences identified in Tunisian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ohno et al (2015) reported that CYP4F22 is responsible for the generation of acylceramide through ω-hydroxylation of long-chain fatty acids [18]. Recently, a CYP4F22 genetic variant associated with lamellar ichthyosis was reported in a Tunisian family [131]. A missense mutation in exon 8, CYP4F22 Arg243Leu, was suggested to be linked to lamellar ichthyosis and predicted to be a functionally defective variant based on in silico analysis.…”
Section: Role Of the Cyp4 Family In Other Diseasesmentioning
confidence: 99%
“…Since the discovery of CYP4F22 was linked to its association with lamellar ichthyosis [18], genetic studies of CYP4F22 polymorphisms have been undertaken. A CYP4F22 variant, CYP4F22 Arg243Leu, was associated with lamellar ichthyosis in a Tunisian family [131], and further genetic studies should be conducted in clinical settings.…”
Section: Genetic Variants Of the Cyp4 Familymentioning
confidence: 99%
“…Our study showed that several SDs were originally classified as non-syndromic, which was the case for USH in the study cohort. Similarly, comorbidity cases were initially classified as SD, e.g., a co-occurrence of HI and ichthyosis that was primarily suspected as a KID syndrome in one patient ( Sayeb et al, 2019 ). Such findings imply that each isolated deafness could be considered as a SD until proven otherwise.…”
Section: Discussionmentioning
confidence: 99%